MENINGKATKAN PERILAKU PENGELOLAAN KEUANGAN MAHASISWA MELALUI FINANCIAL LITERACY DAN FINANCIAL SEL EFFICACY - Suwatno, Suwatno; Waspada, Ika Putera; Mulyani, Heni (JPAK : Jurnal Pendidikan Akuntansi dan Keuangan, 2020)
AbstractThis study aims to analyze the factors that influence student financial management behavior predicted from financial literacy and financial self-efficacy of students, so that financial management behavior can be improved through these factors. The research method used is a quantitative design with an ex post facto approach through multiple regression techniques. Research data collection techniques using a questionnaire. The population and sample of research are students of Bachelor degree of the Faculty of Economics and Business Education, Students of the Master and Doctoral degree of Economic Education Study Programs, and Students of the Master and Doctoral degree of Management Study Programs at Universitas Pendidikan Indonesia. The number of samples was determined using the purposive sampling method. Based on the results of the study note that financial literacy and financial self-efficacy have a positive and significant effect on student financial management behavior. This means that the financial management behavior of student can be determined by the existence of financial literacy and financial self-efficacy.Keywords. financial literacy; financial self-efficacy; financial management behaviour. AbstrakPenelitian  ini  bertujuan  untuk  menganalisis  faktor-faktor  yang  mempengaruhi  perilaku pengelolaan keuangan mahasiswa dilihat dari literasi  keuangan  dan financial self-efficacy  mahasiswa, sehingga perilaku pengelolaan keuangan dapat ditingkatkan melalui faktor-faktor tersebut.  Metode  penelitian  menggunakan  rancangan  kuantitatif  dengan  pendekatan  ex post facto  melalui  teknik  multiple regression. Teknik pengumpulan data penelitian meggunakan kuesioner.  Populasi dan sampel penelitian adalah mahasiswa Fakultas Pendidikan Ekonomi dan Bisnis S1, Program Studi Pendidikan Ekonomi S2 dan S3, serta Program Studi Manajemen S2 dan S3 pada Universitas Pendidikan Indonesia. Jumlah sampel ditentukan dengan menggunakan metode purposive sampling. Berdasarkan hasil penelitian diketahui bahwa literasi keuangan dan financial self-efficacy berpengaruh positif dan signifikan terhadap perilaku pengelolaan keuangan mahasiswa. Ini berarti bahwa perilaku pengelolaan keuangan mahasiswa dapat ditentukan oleh adanya financial literacy dan financial self-efficacy.Kata kunci. financial literacy; financial self efficacy; perilaku pengelolaan keuangan.